Answer:
x < -7
Step-by-step explanation:
2(4x + 1) < 3(2x - 3)
Distributive Property:
8x + 8 < 6x - 6
Subtract on Both Sides:
8x + 8 < 6x - 6
- 6x -6x
--------------------
2x + 8 < - 6
-8 -8
---------------
2x < -14
Divide on Both Sides:
2x < -14
--- ---
2 2
x < -7
60-75%= 45
So 60-45=15
15 people used credit cards
Y = x + 1
y = 2x - 1
basically we r going to sub in one y for another
x + 1 = 2x - 1
1 + 1 = 2x - x
2 = x
now we sub 2 in for x in either of the original equations to find y
y = x + 1
y = 2 + 1
y = 3
so ur solution is (2,3)
Let Cynthia's age be C, then Abigail's age A
since Abigail is 8 years older, her age A = C+8.
20 years ago Cynthia's she was C-20 and Abigail was A-20=3(C-20)
A-20=3C-60
A=3C-40
but we just said A=C+8
so 3C-40=C+8
2C=48
C=24
A=24+8=32
Cynthia's age is 24 and Abigail's age is 32